Analisis Manajemen Risiko Pembiayaan Musyarakah di PT. BPRS Haji Miskin Pandai Sikek - Fadhilah Fitria; Sandra Dewi (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to identify the risks that will arise due to fraudulent practices and breach of contract will be carried out by clients during musyarakah financing. This text also aims to explore how the implementation of risk management can reduce the risks that will occur in the PT. BPRS Haji Miskin Pandai Sikek is a microfinance institution that aims to provide services to the underprivileged population in the Sikek area. In this study, the qualitative method was chosen by the author as the approach that will be used to carry out their research. In this paper, the author uses two types of primary data. Initially, primary information will be obtained directly from primary sources, such as written records and direct observations at the research site. Furthermore, primary information will be obtained through library studies or by referring to relevant books on Islamic banking and related subjects. In this study, the analytical method was used by the researchers. Based on the study, it was reported that fraud and default by customers in musyarakah financing present two types of risks, namely financing risk and operational risk. The implementation of risk management in musyarakah financing will be carried out by a specific PT company. In order to implement the precautionary principle, BPRS Haji Miskin Pandai Sikek utilizes the standard operating procedure (SOP) instructions that have been decided. The risk management process includes four stages, namely risk detection, risk assessment, risk management, and risk monitoring. The principle of the five Cs (character, capacity, capital, collateral and condition of economy) is used in this process.